Comparative analysis of ChatGPT and Gemini (Bard) in medical inquiry: a scoping review - Fattah, Fattah H.; Salih, Abdulwahid M.; Salih, Ameer M.; Asaad, Saywan K.; Ghafour, Abdullah K.; Bapir, Rawa; Abdalla, Berun A.; Othman, Snur; Ahmed, Sasan M.; Hasan, Sabah Jalal; Mahmood, Yousif M.; Kakamad, Fahmi H. (Frontiers in Digital Health, 2025)
IntroductionArtificial intelligence and machine learning are popular interconnected technologies. AI chatbots like ChatGPT and Gemini show considerable promise in medical inquiries. This scoping review aims to assess the accuracy and response length (in characters) of ChatGPT and Gemini in medical applications.MethodsThe eligible databases were searched to find studies published in English from January 1 to October 20, 2023. The inclusion criteria consisted of studies that focused on using AI in medicine and assessed outcomes based on the accuracy and character count (length) of ChatGPT and Gemini. Data collected from the studies included the first author's name, the country where the study was conducted, the type of study design, publication year, sample size, medical speciality, and the accuracy and response length.ResultsThe initial search identified 64 papers, with 11 meeting the inclusion criteria, involving 1,177 samples. ChatGPT showed higher accuracy in radiology (87.43% vs. Gemini's 71%) and shorter responses (907 vs. 1,428 characters). Similar trends were noted in other specialties. However, Gemini outperformed ChatGPT in emergency scenarios (87% vs. 77%) and in renal diets with low potassium and high phosphorus (79% vs. 60% and 100% vs. 77%). Statistical analysis confirms that ChatGPT has greater accuracy and shorter responses than Gemini in medical studies, with a p-value of <.001 for both metrics.ConclusionThis Scoping review suggests that ChatGPT may demonstrate higher accuracy and provide shorter responses than Gemini in medical studies.